Using Integrative Career Construction Counselling to Promote Autobiographicity and Transform Tension into Intention and Action - Jacobus G. Maree (MDPI AG, 2022)
This article reports on the use of integrative career counselling to promote autobiographical reasoning in a purposively sampled gifted 16-year-old female learner with moratorium career identity status. I implemented an explanatory, mixed-methods (QUALITATIVE-quantitative; uppercase denoting the bigger weighting given to the qualitative aspect) research design and used qualitative and quantitative career construction counselling techniques and methods and quantitative career construction counselling techniques and methods and strategies to construct data. The Maree Career Matrix (MCM) was used to gather the participant's career interests ("scores") quantitatively, and the Career Interest Profile (CIP) was used to elicit her micro-narratives ("stories") qualitatively. An adapted version of thematic data analysis was used to analyse the data. The intervention promoted the participant's (self-)reflection and reflexivity, transformed her tension into intention, led to an increase in her career options, and helped her revitalise her sense of meaning, purpose, and positivity. While the findings are encouraging, future (longitudinal) research is needed to establish the long-term influence of the intervention espoused here.